2021
DOI: 10.1111/tme.12771
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to blood product transfusion guidelines—An observational study of the current transfusion practice in a medical intensive care unit

Abstract: Background Blood transfusions though life‐saving are not entirely benign. They are the most overused procedure in the hospital and have been under scrutiny by the ‘Choosing Wisely campaign’. The strict adoption of restrictive transfusion guidelines could improve patient outcomes while reducing cost. Objectives In this study, we evaluate adherence to restrictive transfusion guidelines, along with hospital mortality and length of stay (LOS) in transfusion events with a pre‐transfusion haemoglobin (Hb) ≥7 g/dl. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[5][6][7][8] This recommendation remains based on low-quality evidence and is currently a conditional recommendation per recently published American College of Gastroenterology society guidelines. 9 Therefore, PRBC transfusion practices remain poorly defined and are highly variable in practice, [10][11][12] and many patients with upper GI bleeding are inappropriately transfused. 13 From a pathophysiological standpoint, over-transfusion is likely to be of greatest concern in patients with variceal upper GI bleeding due to its resultant increase in portal pressure, which in turn may cause re-bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] This recommendation remains based on low-quality evidence and is currently a conditional recommendation per recently published American College of Gastroenterology society guidelines. 9 Therefore, PRBC transfusion practices remain poorly defined and are highly variable in practice, [10][11][12] and many patients with upper GI bleeding are inappropriately transfused. 13 From a pathophysiological standpoint, over-transfusion is likely to be of greatest concern in patients with variceal upper GI bleeding due to its resultant increase in portal pressure, which in turn may cause re-bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transfusion practice changed over the last decade, and the general approach has become more restrictive compared with the years 2014 and 2015. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…The mortality was increased in the group of patients with a pretransfusion Hb at least 7 g/dl who received RBCs for acute blood loss and the length of stay was longer in patients receiving transfusions for chronic blood loss. The data point out the potential of clinical and economic improvements by guideline adherence [8 ▪▪ ].…”
Section: Transfusion Triggers: Is Hemoglobin Enough?mentioning
confidence: 96%
“…Today's most practiced transfusion triggers published by Hébert et al in 1999 recommend an Hb threshold for RBC transfusions of 7 g/dl and a target concentration of 7–9 g/dl [2]. Although the body of evidence, which supports this strict transfusion guideline is substantial and still growing [3–7], a recent observational study by Sadana et al [8 ▪▪ ] has shown that about 30% of administered RBC transfusions in an ICU were not compliant with these guidelines. The mortality was increased in the group of patients with a pretransfusion Hb at least 7 g/dl who received RBCs for acute blood loss and the length of stay was longer in patients receiving transfusions for chronic blood loss.…”
Section: Transfusion Triggers: Is Hemoglobin Enough?mentioning
confidence: 99%